Variasi Bahasa dalam Whatsapp Mahasiswa kepada Dosen dan Implikasinya terhadap Pembelajaran - Resta Niriza; Iing Sunarti; Eka Sofia Agustina (FKIP Universitas Lampung, 2018)
The purpose of this research is to describe language variations in WA students to lecturers of Indonesian Language and Literature education and their implications to learning Indonesian Language in high school. The method used in this research is descriptive method by using qualitative approach. The results of the research show that there are variations of language used by students to lecturers, language variations in terms of speakers (1) dialects, for example